RESEARCH ON ACCURATE MODELING OF HYDROSTATIC MOTORIZED SPINDLE BASED ON RESPONSE SURFACE OPTIMIZATION ALGORITHM - SHEN ZhiDong; DU Xiong; LI HaoLin; CAO WenJie; CUI Yi (Jixie qiangdu)
In solving the boundary conditions of a hydrostatic motorized spindle, there are some certain errors between the boundary conditions calculated by the traditional empirical formula and the actual conditions. In order to solve this problem, an optimization algorithm based on response surface is proposed in this paper, which is based on the idea of composite experimental design. The mathematical models of air gap heat transfer coefficient between stator and rotor, forced convection heat transfer coefficient of spindle inner hole and temperature are established, which is also called the mathematical model of temperature field. By using ANSYS Workbench simulation analysis software, load the optimized convective heat transfer coefficient into the simulation model to solve the temperature field of the hydrostatic motorized spindle to solve the temperature field of the hydrostatic motorized spindle. After selecting the sensor measuring points for temperature measurement, the results are compared with the simulation results. The results show that: the maximum error between the front bearing simulation temperature measurement point and the experimental temperature point is only 9.41%, and the maximum error between the rear bearing measurement point and the experimental temperature point is 3.09%. And it verifies the effectiveness and reliability of the method to improve the simulation accuracy of the hydrostatic motorized spindle.